Aged care communicating with family and carers - Charewicz, Stephanie; Ferla, Cath.; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2010)
This program presents approaches and interpersonal skills for the successful care of older Australians. It discusses the combining of informal care arrangements by family with formal aged care services.
Director, Stephanie Charewicz; writer, Cath Ferla; senior producer, Pru Burns; executive producer, Simon Garner.
Voice over artists, Louise Sheldon, Stephanie Charewicz,Thomas Elliott.
Keywords: Caregivers -- Family relationships; Older people -- Care; Older people -- Communication; Aged -- psychology; Communication; Family Relations; Health Services for the Aged; Professional-Patient Relations